Influence of Interval From Calving and Season on Follicular Development, Onset of Oestrus, Conception and Embryonic Mortality During Early Post Partum Period of Cross Bred Cows Under Humid Tropical Climate - Ibraheem Kutty , Cholakkal (The Indian Journal of Animal Reproduction, 2025)
Dairy cows suffer extreme physiological stress during the early stages of lactation depending on the milk yield and climatic adversities, delaying post-partum (PP) fertility. The present study intended to assess the influence of interval from calving and seasons on the resumption of PP fertility. Reproductive ultrasonography of eight early PP cows each was performed every week and continued year-round replacing four cows every month. Details of ovarian structures, oestrus detected, AI done, conception, and embryonic loss were analyzed for variations between weeks of early PP and across seasons. A total of 381 ultrasonography (USG) checks revealed functionally active ovaries throughout the period of study having tiny follicles, prominent antral follicles, and evidence of recent ovulation in 99.23%, 94.17%, and 64.56% respectively. Functionally active follicles were highest during summer and lowest in post-summer (P<0.05) attributable respectively to the direct and delayed effect of thermal stress (TS). Oestrus and conceptions were almost uniform across the weekly intervals, while AI done and conception were lowest (28.57%) during summer. Overall conception of AI and embryonic loss were 48.71 % and 21.05 % respectively and all the embryonic losses occurred before 35 days PP. In spite of the highest conception rate (75.00 %), the embryonic loss was maximum (40.00 %) during post-sum mer, being the delayed impact of TS. To conclude, even though ovaries are functionally active throughout the early PP period, seasons of direct and delayed effect of TS seriously affect the fertility of cross-bred dairy cows under the humid tropical climate.